2015
DOI: 10.1093/abbs/gmv053
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol contributes to the accumulation of myeloid-derived suppressor cells in blood by promoting TNF-α secretion

Abstract: Estrogens are strongly implicated in gender differences in immune responses by influencing the development and activation of immune cells. Recent studies have shown that myeloid-derived suppressor cells (MDSCs), derived from CD11b + Gr-1 + myeloid cells under pathological conditions, play vital roles in modulating immune responses. However, it is still unknown the effects of estrogens on MDSCs. In the present study, we investigated the effects and mechanisms of estrogens on regulating the accumulation of MDSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
2
16
2
2
Order By: Relevance
“…However, all these studies are still limited to animal experiments. • Strikingly, in our previous study, proportions of MDSCs were expanded in SLE patients [6], which was in contrast with other studies by reporting a reduction in MDSC numbers in lupusprone (NZB×NZW)F1 mice. As is well known, MDSCs can be further divided into M-MDSCs and G-MDSCs.…”
Section: Clinical Perspectivescontrasting
confidence: 99%
See 1 more Smart Citation
“…However, all these studies are still limited to animal experiments. • Strikingly, in our previous study, proportions of MDSCs were expanded in SLE patients [6], which was in contrast with other studies by reporting a reduction in MDSC numbers in lupusprone (NZB×NZW)F1 mice. As is well known, MDSCs can be further divided into M-MDSCs and G-MDSCs.…”
Section: Clinical Perspectivescontrasting
confidence: 99%
“…However, these studies draw a different conclusion on the proportions of MDSCs in SLE [3][4][5]. Strikingly, in our previous study, the proportion of MDSCs was expanded in SLE patients [6], which was in contrast with other studies that found a reduction in MDSC numbers in lupus-prone (NZB×NZW)F1 mice. In addition, previous study failed to explore the mechanism of function changes in MDSCs in SLE [3][4][5].…”
Section: Introductioncontrasting
confidence: 81%
“…9,10 However, E2 and MDSCs mutualistic functional relationship during pregnancy and in pathological setting like early miscarriage is still unexplored story and present work is a forward step to understand the same. Recent reports in cancer patients have shown that 17β-estradiol (E2) promotes accumulation of MDSCs in blood through the secretion of TNF-α.…”
Section: Role Of Mdscs Was Firstmentioning
confidence: 90%
“…Recent reports in cancer patients have shown that 17β-estradiol (E2) promotes accumulation of MDSCs in blood through the secretion of TNF-α. 9,10 However, E2 and MDSCs mutualistic functional relationship during pregnancy and in pathological setting like early miscarriage is still unexplored story and present work is a forward step to understand the same. E2 and P4 is also a potent regulator of Th1/Th2 cytokines balance and help in the production of Th2/anti-inflammatory cytokines which are helpful in building a conducive systemic milieu for healthy pregnancy.…”
Section: Introductionmentioning
confidence: 90%
“…+ GR-1 + ) [28] . 目前认 为, MDSCs发挥免疫抑制功能主要依赖于精氨酸酶 (ARG-1) [29] , 一氧化氮合酶(iNOS) [28] , ROS [30,31] , IL-1β [32] , IDO [33] 等因子的产生. 10 0 10 0 10 1 10 2 10 3 10 4 Q1 10 0 10 0 10 1 10 2 10 3 10 4 Q1 3.50% [34] .…”
Section: 抗原Gr-1和cd11b的细胞(cd11bunclassified